Extensive thoracic vertebral and chest wall metastases as the initial presentation of breast cancer: a case report and literature review - Kenzhegulov, Yergen N.; Zhamoldin, Daniyar K.; Aleinikov, Victor G.; Kerimbayev, Talgat T.; Zhetpisbaev, Berik; Akshulakov, Serik (Frontiers in Oncology, 2025)
Metastatic involvement of the bones remains the most common form of distant metastasis in breast cancer, largely due to the anatomical and functional characteristics of the thoracic spine, ribs, and sternum. These structures are notable for their high content of red bone marrow, rich vascularization, and their connection to Batson’s venous plexus, all of which facilitate their early involvement in oncologic dissemination. In certain cases, multiple metastases in the thoracic skeleton may represent the first and sole clinical manifestation of an undiagnosed malignant process, presenting considerable diagnostic challenges at the initial presentation in patients without a known oncologic history. A 60-year-old female patient presented with severe thoracic back pain. Imaging revealed multiple lytic lesions in the vertebral bodies of the thoracic spine, ribs, and sternum. The initial differential diagnosis included multiple myeloma and bone metastases. The patient underwent minimally invasive neurosurgical intervention involving spinal canal decompression and percutaneous vertebral biopsy. A percutaneous vertebral biopsy confirmed the presence of undifferentiated carcinoma. Subsequent PET-CT identified a metabolically active lesion in the breast, establishing the primary diagnosis, followed by the initiation of systemic therapy. This case, in conjunction with a review of the current literature, highlights the diagnostic complexity of presentations where pain is the sole initial symptom of an undetected malignancy. Such situations demand a high index of oncologic suspicion from the outset, timely application of advanced imaging modalities such as MRI and PET-CT, mandatory histological verification of affected regions, and strong interdisciplinary coordination to achieve accurate diagnosis and formulate a personalized treatment strategy.